2017
DOI: 10.1371/journal.pone.0176382
|View full text |Cite
|
Sign up to set email alerts
|

SF3B1 is a stress-sensitive splicing factor that regulates both HSF1 concentration and activity

Abstract: The heat shock response (HSR) is a well-conserved, cytoprotective stress response that activates the HSF1 transcription factor. During severe stress, cells inhibit mRNA splicing which also serves a cytoprotective function via inhibition of gene expression. Despite their functional interconnectedness, there have not been any previous reports of crosstalk between these two pathways. In a genetic screen, we identified SF3B1, a core component of the U2 snRNP subunit of the spliceosome, as a regulator of the heat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
(42 reference statements)
4
15
0
Order By: Relevance
“…Our observations raise the possibility that splicing disruptions leading to readthrough transcription represent a common molecular link underlying DoG transcription. In support of this, SF3B1 is a stresssensitive splicing factor that responds to heat shock (Kim Guisbert and Guisbert, 2017). In addition, we note that these cellular stresses and viral infections also led to a broad repression of transcription and gene expression, as observed here upon splicing disruption.…”
Section: Pladb-induced Transcriptional Alterations Resemble Other Strsupporting
confidence: 73%
“…Our observations raise the possibility that splicing disruptions leading to readthrough transcription represent a common molecular link underlying DoG transcription. In support of this, SF3B1 is a stresssensitive splicing factor that responds to heat shock (Kim Guisbert and Guisbert, 2017). In addition, we note that these cellular stresses and viral infections also led to a broad repression of transcription and gene expression, as observed here upon splicing disruption.…”
Section: Pladb-induced Transcriptional Alterations Resemble Other Strsupporting
confidence: 73%
“…At present, studies on the important role of SF3B1 have mainly focused on humans and animals, while its role in plants has not been reported. Kim Guisbert et al [64] revealed that SF3B1 regulates the activity of the heat shock transcription factor (HSF1) via mRNA splicing to enhance stress-sensitive abilities. In this study, eight phosphosites in the SF3B1 were up-expressed in Cd + N treated plants, which indicated that SF3B1 may modulate poplar plants' resistant to Cd stress by mRNA splicing at the transcriptome.…”
Section: Exogenous Nitrogen Promoted Protein Phosphorylation To Enhanmentioning
confidence: 99%
“…As such, the spliceosome has emerged as an attractive target for anticancer treatment [16]. SF3b1 is a principal player in the spliceosome and a target of inhibitor compounds [17,18]. Several spliceosome modulators have already been identified [19].…”
Section: Introductionmentioning
confidence: 99%